Incidence and Anatomy of Tubarial Salivary Gland in Local Indian Population - , Sayali Goraksha Lokhande, Sunil Surendraprasad Mishra, Bharti Eknath Helge, Ashutosh Sanjay Dighe (Turkish Journal of Gastroenterology 1, 2023)
Background: Tubarial salivary glands were frst discovered and reported in the year 2021 by Valstar et al and were named “tubarial salivary glands” depending upon their location. The presence of these glands is believed to play a major role in helping oncologists and otorhinolaryngologists in radiation therapy planning and surgical management, thus improving the quality of life of patients. The main objective is to study the incidence of tubarial salivary glands in the local Indian population and assess its anatomical characteristics using magnetic resonance imaging (MRI) scans.Methods: Magnetic resonance images of 60 scans were examined from the database, and analysis was performed using the T2 weighted (T2W) sequences. The presence of the tubarial salivary glands, their position and number, and the size of the glands were examined on the MRI scans by an experienced radiologist.Results: The glands were identifed bilaterally in all 60 MRI scans. The average dimensions for the right and left glands were 39.4 mm × 15.3 mm × 6.5 mm and 38.9 mm × 15.4 mm × 6.6 mm, respectively. The age-wise distribution of the presence of glands showed a statistically signifcant increase in the size of the glands with increasing age groups (P < .05).Conclusion: We observed a soft tissue structure in the anatomical site of the previously documented tubarial salivary glands on T2W MRI images. The structure’s intensity was comparable to that of a typical parotid gland. The fndings of our study offer crucial evidence in favor of the long-contested presence and identifcation of a novel salivary gland.Cite this article as: Lokhande SG, Mishra SS, Helge BE, Dighe AS. Incidence and anatomy of tubarial salivary gland in local indian population. ENT Updates. 2023;13(3):46-50.